The Interplay of Morality and Social Order in Al-Ghazali’s Thought - Taja, Nadri; Hakim, Arif; Faqihuddin, Achmad (West Science Social and Humanities Studies, 2025)
This article examines the close relationship between morality and social order in the thoughts of Al-Ghazali, a great classical Islamic thinker who combines ethical, political, and spiritual dimensions within the community development framework. This research used a literature study method to critically analyze Al-Ghazali's main works, such as Ihya 'Ulum al-Din, Nasihat al-Muluk, and Al-Mustazhiri. The study results show that Al-Ghazali places morality as the foundation for creating a just, orderly, dignified society. Morality is seen as a personal responsibility and a controlling element in leadership and socio-political life. Al-Ghazali emphasized the importance of moral leaders, moral education as a social transformation, and the role of religion in maintaining public civility. He also viewed morality as a form of resistance to social damage, especially in the face of the decadence of political and religious elites. This article concludes that Al-Ghazali's thoughts are relevant to the contemporary context as a model of social reconstruction based on Islamic values, spirituality, and ethical justice. Hopefully, these findings can enrich the discourse on developing a more integrative, moderate, and sustainable Islamic society.